2019
DOI: 10.1002/bse.2321
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability reporting, materiality, and accountability assessment in the airport industry

Abstract: Air travel is, nowadays, recognized as being one of the most popular modes of transport. Air transport is among the most significant contributors to the world gross domestic product and is accountable for a great environmental and social impact. Driven by the well‐established sustainability discourse and the vital role businesses can play in disseminating the sustainable development concept, this paper attempted to map airport industry's most material operational aspects and assess airport operators' accountab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 41 publications
2
46
0
3
Order By: Relevance
“…Hu et al (2011) showed that the principle of clarity has scored highly in Taiwanese firms, whereas materiality principles need to be examined through more detailed research. By examining materiality principles in European airports, Karagiannis et al (2019) identified high materiality on customer focus, financial sustainability, and business continuity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hu et al (2011) showed that the principle of clarity has scored highly in Taiwanese firms, whereas materiality principles need to be examined through more detailed research. By examining materiality principles in European airports, Karagiannis et al (2019) identified high materiality on customer focus, financial sustainability, and business continuity.…”
Section: Discussionmentioning
confidence: 99%
“…It is a time-demanding procedure that often requires expert personnel (Karagiannis et al, 2019). Therefore, organizations should make more efforts and focus on defining the report content in line with their most material aspects (Bebbington, 2001).…”
Section: Assessing Csr Reportsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study has also revealed that some of the airlines reported CSR initiatives following the legal and regulatory guidelines, while others chose not to [6]. Recently, a change of CSR reporting practice is noted where airlines are found to report more on social and economic responsibilities [24,61,64]. To fully reveal the changing landscape of CSR reporting in the aviation industry, a longitudinal study on the reporting of major CSR issues is highly warranted.…”
Section: The Need For Researching Into Csr Reporting In Aviation Indumentioning
confidence: 99%
“…The first research question is proposed to reveal the trend and changes of CSR reporting along the three major CSR dimensions namely economic, environment and social issues in the airline industry [6,24,28,61,[63][64] from 2013 to 2017. RQ1: What was the trend of CSR reporting in the economic, environment and social dimensions in the airline industry from 2013 to 2017?…”
Section: Research Questions and Hypothesismentioning
confidence: 99%